PERSEPSI WISATAWAN TENTANG PROMOSI DAN FASILITAS OBJEK WISATA MUSEUM ADITYAWARMAN DI KOTA PADANG - Marvidola, Triska; Kasmita, Kasmita; Waryono, Waryono (Journal of Home Economics and Tourism, 2014)
This study aimed to describe the perception of tourists on promotion and facilities Adityawarman museum in the city of Padang which includes indicators: Advertising (advertising), form, function, location, and quality. As the population is a tourist attraction in the city of Padang Museum Adityawarman numbering 77,389 people. Sampling technique as for the non-probability sampling is incidental sampling with number 100. Data was collected using a questionnaire and analyzed through descriptive analysis with categorization method based on the average assessment scores. Based on the analysis of data traveler perceptions about promotion Adityawarman museum in the city of Padang relatively less well with the average of 2.12 and a variable facility is quite good with an average of 3.37. Where the indicator 1) form of tourist facilities belong to either category with an average value of (3.63), 2) belong to the category of facility function quite well with the average value of (3.40), 3) the location of facilities classified the category quite well with the average value of (3.21), 4) the quality of tourist facilities belong to the category of fairly good with an average value of 3.32.Keyword: Perception, Promotion and Facility, Tourist.